2020
DOI: 10.1016/j.cell.2020.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Selection and Constraint on Human Knee Chondrocyte Regulation Impacts Osteoarthritis Risk

Abstract: During human evolution, the knee adapted to the biomechanical demands of bipedalism by altering chondrocyte developmental programs. This adaptive process was likely not without deleterious consequences to health. Today, osteoarthritis occurs in 250 million people, with risk variants enriched in non-coding sequences near chondrocyte genes, loci that likely became optimized during knee evolution. We explore this relationship by epigenetically profiling joint chondrocytes, revealing ancient selection and recent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
110
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 186 publications
3
110
0
1
Order By: Relevance
“…Secondly, Huang et al's meta-analysis explores the association between all kinds of osteoarthritis and GDF5 rs143383 polymorphisms, which cannot precisely describe the relationship between GDF5 rs143383 polymorphisms and the susceptibility of knee osteoarthritis [12]. Although genetic variants can have different effect sizes in different populations, as is shown for GDF5 for African populations vs Eurasian populations [43][44][45], it is highly unlikely that this is the case, based on the data presented by the authors. These studies focused on apes, so there is still a gap between apes and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, Huang et al's meta-analysis explores the association between all kinds of osteoarthritis and GDF5 rs143383 polymorphisms, which cannot precisely describe the relationship between GDF5 rs143383 polymorphisms and the susceptibility of knee osteoarthritis [12]. Although genetic variants can have different effect sizes in different populations, as is shown for GDF5 for African populations vs Eurasian populations [43][44][45], it is highly unlikely that this is the case, based on the data presented by the authors. These studies focused on apes, so there is still a gap between apes and humans.…”
Section: Discussionmentioning
confidence: 99%
“…OA is the most common type of arthritis with in ammatory disease in the synovial joints (32,33) . It is characterized by gradual degeneration of articular cartilage and changes in the structure and function of the entire joint (34,35) . In recent years, it has been reported that the canonical SMAD signaling of the TGF-β signaling pathway contribute signi cantly to cartilage maintenance and repair.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, Xin Huang's meta-analysis explores the association between all kinds of osteoarthritis and GDF 5 rs143383 polymorphisms, which can't precisely describe the relationship between GDF 5 rs143383 polymorphisms and the susceptibility of knee osteoarthritis [12]. Although genetic variants can have different effect sizes in different populations, as is shown for GDF5 for African populations vs Eurasian populations [43][44][45], it is highly unlikely that this is the case, based on the data presented by the authors. These studies focused on apes, so there is still a gap between apes and humans.…”
Section: Discussionmentioning
confidence: 99%